Detection of Immunoglobulin Gene Rearrangement in Acute Lymphoblastic Leukemia by Polymerase Chain Reaction - Nayyar, Ayesha; Ahmed, Suhaib (International Journal of Pathology, 2018)
Background: The objective of the study was to evaluate a qualitative PCR based method for detection of clonalimmunoglobulin gene rearrangement in patients of acute lymphoblastic leukemia. It was a descriptive Cross sectionaland it was conducted at Armed Forces Institute of Pathology Rawalpindi between Aug 2009- Jan2010.Method: 61 patients with acute lymphoblastic leukemia were studied. Genomic DNA was extracted from theperipheral blood, bone marrow aspirate/unstained bone marrow smears. PCR amplification of the IgH gene wasdone by a VH primer homologous with a highly conserved sequence near the 3’ end of the FR3 region and a consensussequence JH primer. The amplified DNA was seen by electrophoresis on 6% polyacrylamide gel.Results: A sharp clonal band ranging from 90-200 bp indicated a positive reaction. At the time of diagnosis 50out of the 61 patients (82%) showed clonal immunoglobulin gene rearrangement by qualitative PCR using a singlepair of primers. Eleven (18%) patients did not show the Ig gene rearrangement.Conclusion: Clonal Ig gene rearrangements can be demonstrated in a vast majority of patients of Acute LymphoblasticLeukemia by simple PCR using a single pair of primers.